Analysis of The Effect of Regional Levies and Regional Taxes on Regional Expenditure in North Sumatra Province - Zulsahyani Limbong; Nancy Mayriski Siregar; An Suci Azzahra (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the effect of regional retribution and regional taxes on regional expenditure in regencies and municipalities in North Sumatra Province. In the era of fiscal decentralization, increasing Local Own-Source Revenue (PAD) is a key indicator of fiscal independence and the capacity of local governments to finance development and public services. Regional taxes and regional retributions constitute the main components of PAD and are expected to enhance local governments’ ability to fund public expenditure. This research employs a quantitative approach using multiple linear regression analysis based on secondary data derived from the Regional Budget Realization Reports (APBD) of regencies and municipalities in North Sumatra over a specific period. The independent variables are regional taxes and regional retributions, while the dependent variable is regional expenditure. The analysis includes descriptive statistics, classical assumption tests, partial tests (t-test), simultaneous test (F-test), and the coefficient of determination (R²). The results indicate that regional taxes have a positive and significant effect on regional expenditure, suggesting that higher tax revenue increases local governments’ spending capacity. Regional retributions also show a positive effect, although their contribution is relatively smaller compared to regional taxes. Simultaneously, regional taxes and retributions significantly influence regional expenditure. These findings highlight the importance of optimizing tax and retribution management to strengthen fiscal capacity and improve the effectiveness of regional spending. The study provides policy implications for local governments to intensify and expand revenue sources in order to support sustainable regional development.